Development of Smart Games Themes The Beauty of Diversity in My Country for Grade IV SD/MI students - Eleonora Ragil Feri Setyari; Dwi Kameluh Agustina; Maria Ulfa Yudha Julistiana (JOSAR (Journal of Students Academic Research), 2022)
Based on the results of observations at UPT SDN Sumberdiren 02, it is known that thelearning media used so far are still less varied, so creative and interesting media areneeded. At that school the Smart Game Media had never been used. The purpose ofthis study is to explain the development of Smart Games for SD/MI students. Theresearch design used is Research and Development (R&D). The development modelused is the Borg and Gall model proposed by Sugiyono which is limited to the seventhstage, namely product revision. The results showed that the assessments of mediaexperts, linguists and material experts were respectively 85.5%, 87% and 80%.Student response 89%. Students' reading interest increased by 99%, from the averageresult of 2.63 to 5.27. The results of this study have reached the criteria set out inprevious studies, namely 9.3%. 87% student interest in reading questionnaire. So it isknown that Smart Games can increase the learning interest of SD/MI student